Peningkatan Aktivitas Belajar Siswa pada Pelajaran IPA dengan Pelaksanaan Lesson Study - Hamedda Fatmawati Alhusna; Sri Haryanto; Firdaus Firdaus (SPEJ (Science and Physic Education Journal), 2022)
Abstract: The purpose of this study was to determine whether there was an increase in a student learning activity in science subjects for Class VIII SMP by implementing Lesson Study. This type of research is a type of cooperative qualitative research. The population in this study were students in classes VIII B and VIII C for the 2022/2023 Academic Year as many as 20 students in each category. The results showed that the observed student learning activities from the eight indicators experienced an increase before and after the implementation of the Lesson Study, with an average value of student learning activities in the second sample class meeting of 68.30%, with the category of achievement quite active. The experimental sample class implementing the Lesson study obtained an average value of 79.91% from the two meetings with the Active achievement category. In conclusion, the performance of the Lesson Study can increase student learning activities in science class VIII at SMP AL-Madina Boarding School Wonosobo. Keywords: Learning Activities, Science, Lesson Study